Exploring Transnational Realities in the Lives of Faroese Youngsters - Erika Anne Hayfield (Nordic Journal of Migration Research, 2017)
Faced with the reality of youth out-migration in many Northern peripheral areas, there is a need to consider out-migration from a cultural practice viewpoint. I argue that the emergence of a transnational perspective in young people is a key feature of the Faroe Islands’ culture of migration, and that the young people come to have a transnational perspective, even before they become transnationals. Therefore, migration can be viewed as a defining characteristic of growing up in the Faroe Islands. Based on interviews with youngsters in two age groups, 14-15 years old and 18-24 years old, this study explores how young people construct their futures in a culture of migration. More specifically, the study focuses on the building of transnational life paths as a deeply embedded phenomenon for young people in constructing the trajectory to adulthood.